Aspek Kebudayaan Material dan Non Material pada Gerai Kopi Starbucks - Rifka Pratama (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2019)
Whether it is on a limited or a mass scale, coffee has long been an industrial commodity. In the social context, it can be even a social glue of interaction between individuals or communities. The claims have, indeed, implied the value of the beans. Certain elements take part in the making of the so-called coffee popularity. From a cultural perspective, the existence of material and non-material aspects of culture can be the keys. This study aims to identify and to inventory the aspects of material and non-material culture of one of world-famous coffeehouses, Starbucks. The data were obtained through library study. The main data as well as the objects of the study are information contained on the official Starbucks’ website. Other supporting data were taken from other relevant sources. Based on the study, the two aspects of culture, material and non-material, can be found in the American coffee company. The classifications of both were also made to fulfill the need of the further study.